PSPN analiza futsala kot osnova za strateško načrtovanje njegovega razvoja - Lojen, Denis (Šport (Ljubljana), 2021)
Futsal is a sports game, a version of football and a discipoline within the Football Association of Slovenia. The main purpose of the work was to perform an in-depth analysis, which should be the initial phase for strategic planning of further development of futsal in Slovenia. The primary method is descriptive. We also made a SWOT analysis. The first two aspects (advantages and disadvantages) relate to internal factors (organization and operation), and the other two (opportunities and threats) to external factors (competition between sports, lack of playgrounds, tradition). The findings of the analysis indicate conflicting factors. On the one hand, we note an intensive general development - that the number of registered players has been growing in recent years, as well as recreational playing of futsal, with the organization of the European Championship in 2018, success have been achieved at the organizational and competitive level. On the other hand, contrary to this success, we are also monitoring the decline of registered teams in the Slovenian league; national teams have had less activities and matches in recent years than before, in a way, the professional and organizational development of futsal has stagnated. If the discipline in Slovenia wants to further develop, actions are needed. The presented analysis can be an appropriate professional basis for the actors in the Football Association of Slovenia with the formation of the final strategy for the development of futsal in Slovenia.
Keywords: analiza PSPN; analysis; futsal; sport; strategic planning; strateško načrtovanje; SWOT; šport